1989
DOI: 10.1111/j.1365-2621.1989.tb05941.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protein Solubility and Gelation Properties of Chicken Myofibrils during Storage

Abstract: The effect of storage on protein solubility and heat-induced gelation properties of chicken hen breast and leg myofibrils was investigated. Myofibrils suspended in 0.6M NaC1, pH 6.0, showed increasing protein solubility, viscosity, gel strength and water holding capacity with storage at 4°C. However, the effect of storage was most dramatic only during the initial 10 hr for all of the parameters studied. The relative distribution of the proteins comprising the salt soluble protein (SSP) extract changed during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 34 publications
6
64
0
Order By: Relevance
“…As the gel strength decreased beyond this period, the proportion of actin increased progressively. These results are in agreement with those of Martinez et a/ (1986) and Xiong and Brekke (1989), which showed an improved gelling ability as the M/A ratio increased. It is therefore likely that the MHC/A ratio has a major influence on the gelling properties of the actomyosin isolated from fish of different post-mortem history.…”
Section: Electrophoretic Studies On Natural Actomyosin During Ageing supporting
confidence: 95%
See 1 more Smart Citation
“…As the gel strength decreased beyond this period, the proportion of actin increased progressively. These results are in agreement with those of Martinez et a/ (1986) and Xiong and Brekke (1989), which showed an improved gelling ability as the M/A ratio increased. It is therefore likely that the MHC/A ratio has a major influence on the gelling properties of the actomyosin isolated from fish of different post-mortem history.…”
Section: Electrophoretic Studies On Natural Actomyosin During Ageing supporting
confidence: 95%
“…Other authors have observed an increase in the MHC/A ratio of actomyosin of chicken myofibrils during storage for 24 h at refrigerated temperatures in 0.6 M KCl and that this was in parallel with an increase in the gel rigidity of these myofibrils (Xiong and Brekke 1989). Some authors have tried to use the MHC/A ratio as an index for predicting the strength of surimi gels (Martinez et a1 1986).…”
Section: Electrophoretic Studies On Natural Actomyosin During Ageing mentioning
confidence: 96%
“…Their relative solubility is dependent gels that were stronger than those of myosin dependent not only o n ionic strength, pH (Richardson from red (leg) muscle. These findings were substantiated and Jones 1987), species (Amato et al 1989) and postlater by several studies (Fretheim et a1 1986;Foegeding 1987;Xiong and Brekke 1989), although some * To whom correspondence should be addressed.…”
Section: Introductionsupporting
confidence: 67%
“…Viscosity of myosin within pH range from 5.4 to 6.0 [14] and at pH 7.0 [2], myofibrillar proteins at pH 6.5 [19], myofibrils at pH 6.0 [20] and SSP within pH range from 5.75 to 8.0 [25] from chicken or hen breast muscles was greater than from leg/thigh muscles. The differences in viscosity of myosin from white and red muscles could be attributed to different shapes of these molecules.…”
Section: Introductionmentioning
confidence: 99%